High quality image reconstruction from multiple low quality images - Royyuru Mohana Prasanna Vadan (2014)
The purpose of this project was to implement an image reconstruction procedure from multiple low quality input images. It would integrate concepts of deblocking and deblurring for achieving a high performance in reconstruction.